An efficient frequency-doubled Nd:KLu(WO4)2 laser at 535 nm. (March 2016) - Fu, Qiang; Zhang, Xingyu; Liu, Zhaojun; Cong, Zhenhua; Zhang, Huaijin; Li, Jing; Yu, Haohai; Wang, Weitao
Abstract: An efficient laser diode pumped frequency-doubled Nd:KLu(WO4 )2 laser at 535 nm was demonstrated for the first time. For continuous wave (CW) operation, the obtained maximum output power was 2.4 W and the overall optical-to-optical conversion efficiency with respect to the absorbed pump power was 20.5%. For active Q-switching operation, the obtained maximum average output power was 2.6 W and the conversion efficiency with regard to the absorbed pump power was 26.8%. The corresponding pulse repetition rate (PRR), pulse width, single pulse energy and peak power were 30 kHz, 36.6 ns, 86.7 μJ, and 2.4 kW, respectively. On the basis of rate equations, the characteristics of the actively Q-switched frequency-doubled Nd:KLu(WO4 )2 laser were simulated. The theoretical results of the average output power and pulse width were obtained. They were in agreement with the measured data on the whole. Highlights: A frequency-doubled Nd:KLu(WO4 )2 laser was investigated for the first time. A 2.4 W CW 535 nm laser was obtained with a conversion efficiency of 20.5%. A 2.6 W Q-switched 535 nm laser was obtained at a pulse repetition rate of 30 kHz.